1993
DOI: 10.1016/0014-5793(93)81513-y
|View full text |Cite
|
Sign up to set email alerts
|

Minor‐groove binders are inhibitors of the catalytic activity of DNA gyrases

Abstract: Non-intercalating DNA minor-groove binders may effectively inhibit the supercoiling activity of gyrases by influencing the enzyme recognition and cleavage site on DNA. For gyrase from Streptomyces noursei a wide range of inhibitory potency for different classes of ligands is observed. This can be explained by a number of structural and binding factors of the ligands competing with the gyrase on the target site of DNA, the mechanism of which is different from the classical gyrase inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…It has been shown that minor groove binding drugs may inhibit eukaryotic topoisomerase II (72)(73)(74) and gyrase (75) to a different extent, depending on the ligand structure.lt is quite possible that the effects of minor groove binders on DNA supercoiling play a role in their inhibitory potency on topoisomerase action, which was not recognized in previous studies on the enzymes (72)(73)(74)(75).…”
Section: Various Minor Groove Binders Affect Dna Superhelicity To a Dmentioning
confidence: 96%
“…It has been shown that minor groove binding drugs may inhibit eukaryotic topoisomerase II (72)(73)(74) and gyrase (75) to a different extent, depending on the ligand structure.lt is quite possible that the effects of minor groove binders on DNA supercoiling play a role in their inhibitory potency on topoisomerase action, which was not recognized in previous studies on the enzymes (72)(73)(74)(75).…”
Section: Various Minor Groove Binders Affect Dna Superhelicity To a Dmentioning
confidence: 96%
“…2 demonstrates that in the presence of 1.5 #g/ml CQ, Nt-lm3 and SN-6999 produce downward shifts (CQ in panels A and B, lanes 7-10). Samples were electrophoresed in 1% agarose gels in 50 mM Trisacetate (pH 8.0), 20 mM sodium acetate, 2 mM EDTA, 18 mM NaCl at 30 V/cm for 18 h. Staining of the DNA in EB (0.5 #g/ml), photography and scanning of negatives have been described previously [3]. Gels with CQ contained CQ at concentrations of 1.5 #g/ml or 3 #g/ml in both the gel and the electrophoresis buffer.…”
Section: Enzymesmentioning
confidence: 99%
“…Drug-induced effects on DNA play a role with respect to their interference with enzymes of DNA metabolism, such as topoisomerases [1][2][3]. Binding of small intercalative ligands, such as EB or CQ, to a topoisomer unwinds DNA as a consequence of intercalation and, upon increasing ligand concentration, alter the superhelix density from negatively supercoiled, via the relaxed, to the positive supercoiled state.…”
Section: Introductionmentioning
confidence: 99%
“…Hence it contributes to the study of DNA base–specific interactions. This antibiotic exerts its biological activity by interfering with proteins that regulate replication and transcription processes [3–5].…”
mentioning
confidence: 99%